27.8k views
1 vote
Please help me out with this

Please help me out with this-example-1

2 Answers

2 votes

Answer:

FG = 13

Explanation:

We can write

EF + FG = EG ← substitute values

12 + FG = 25 ( subtract 12 from both sides )

FG = 25 - 12 = 13

User Benjamin Eckstein
by
5.9k points
3 votes

Answer:

FG=13

Explanation:

We can make an equation that looks like this:

EF+FG=EG

Then, we can substitute in the numbers we know:

12+FG=25

Then solve:

FG=25-12

FG=13

Hope I helped soz if I'm wrong ouo.

~Potato.

Copyright Potato 2019.

Trademark ~Potato. 2019.

User Nick Coelius
by
5.2k points